Development of Learning Media Using Google Site in Qur'an Hadith Subjects at Madrasah Aliyah Negeri 1 Medan - Ritonga, Rika Lasmini; Hamid K., Abdul; Endriani, Dewi (CV. Media Inti Teknologi, 2025)
Background: Low student motivation and poor cognitive outcomes in the Qur’an Hadith subject at MAN 1 Medan indicate the need for more interactive learning media. Traditional tools such as PowerPoint and videos are less engaging for digital-native students.Aims: This study aims to develop a Google Sites–based digital learning medium on the topic “Competing in Goodness” tailored for eleventh-grade students to improve learning outcomes and engagement.Methods: The study employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) with 35 students and 3 teachers as participants. Data were gathered through questionnaires, expert validation sheets, and post-tests.Result: The needs analysis showed high student interest in digital media (94%) and strong teacher support (92%). Expert validation indicated high feasibility (91–93%). Trial tests demonstrated increased practicality (up to 94%) and improved post-test scores in the experimental group (82.9) versus the control group (77.0).Conclusion: Google Sites based learning media is valid, practical, and effective for enhancing motivation and cognitive outcomes in Qur’an Hadith education at the senior high school level.